The Superantigen Gene ypm Is Located in an Unstable Chromosomal Locus of Yersinia pseudotuberculosis - Carnoy, Christophe (American Society for Microbiology, 2002)
Yersinia pseudotuberculosis produces YPM (Y. pseudotuberculosis-derived mitogen), a superantigenic toxin that exacerbates the virulence of the bacterium in vivo. To date, three alleles of the superantigen gene (ypmA, ypmB, and ypmC) have been described. These genes are not found in all Y. pseudotuberculosis strains and have a low GC content, suggesting their location on mobile genetic elements. To elucidate this question, the genetic environment of the superantigen-encoding genes was characterized and 11 open reading frames (ORFs) were defined. Sequence analysis revealed that the ypm genes were not associated with plasmids, phages, transposons, or pathogenicity islands and that the superantigen genes were always located in the chromosome between ORF3 and ORF4. Nonsuperantigenic strains exhibited the same genetic organization of the locus but lacked the ypm gene between ORF3 and ORF4. A new insertion sequence, designated IS1398, which displays features of the Tn3 family, was characterized downstream of the ypmA and ypmC genes. A 13.3-kb region containing the ypm genes was not found in the genome of Y. pestis (CO92 and KIM 5 strains). We experimentally induced deletion of the ypm gene from a superantigen-expressing Y. pseudotuberculosis: using the association of aph(3′)-IIIa and sacB genes, we demonstrated that when these reporter genes were present in the ypm locus, deletion of these genes was about 250 times more frequent than when they were located in another region of the Y. pseudotuberculosis chromosome. These results indicate that unlike other superantigenic toxin genes, the Yersinia ypm genes are not associated with mobile genetic elements but are inserted in an unstable locus of the genome.